PC.50 Pain assessment in ventilated and non-ventilated neonates in NICUs across the UK: European Pain Audit in Neonates (Europain). (9th June 2014) - Boyle, EM; Courtois, E; Eriksson, M; Lagercrantz, H; Carbajal, R
Abstract : Background: Neonates undergo many painful procedures during their neonatal intensive care stay. These may include tracheal intubation/ventilation, skin-breaking procedures, drainage/suctioning of body orifices or cavities. Inherent subjectivity and difficulties associated with neonatal pain assessment contribute to a wide variety of assessment tools and clinical practices. To date, these practices have been not studied on a large scale. Objective: To determine current clinical practices for neonatal pain assessment in neonatal units across the United Kingdom (UK). Design/Methods: As part of a European epidemiological observational study on bedside pain assessment practices data were collected for all neonates in participating NICUs until infants left the unit (discharge, death, transfer to another hospital) or for 28 days. Data collection occurred via an online database for 1 month at each NICU. All neonates up to a gestational age of 44 weeks were included. Results: Between February 2013 to May 2013, 66 UK NICUs collected data on 2691 neonates. Of these, 713 received tracheal ventilation and 1978 had spontaneous breathing or non-invasive ventilation. The median (IQR) gestational age of ventilated neonates [32.1 (27.9–38.6)] was less than non-ventilated neonates [37.0 (34.1–39.7), p < 0.001]. Overall, 56.9% of ventilated neonates and 32.5% of non-ventilated neonates received bedside pain assessments (p < 0.001), with use of pain assessments ranging from 0–100% between units. Conclusions: Over half (56.9%) of ventilated neonates and about one third (32.5%) of non-ventilated neonates had pain assessments performed in UK neonatal units. Wide variations in the methods used and rates of pain assessment exist among centres.